La contaminacin atmosfrica en mi comunidad - Aguilar Huaambal, Josue (2021)
The work of professional sufficiency, which I present, has as its supporting theme "Air pollution in my community", said research has been carried out for students of the 2nd grade of secondary education in the area of Social Sciences. Two chapters have been developed, the first being the theoretical support addressing the knowledge of environmental pollution, environmental education, the approach to the area of social sciences, among other knowledge, in the second, the pedagogical support where the learning experience is determined , its moments, as well as the materials and resources used. Culminating in the conclusion that the level of atmospheric pollution in my town is high, a product of the emission of polluting gases and its impact on the health of the population is constant.